IN SILICO ANALYSIS OF TRANSCRIPTION FACTOR BINDING SITES IN PROMOTERS OF GERMIN-LIKE PROTEIN GENES IN RICE - Ilyas, Muhammad; Naqvi, Syed Muhammad Saqlan; Mahmood, Tariq (Archives of Biological Sciences, 2016)
Germins (GERs) and germin-like proteins (GLPs) play important roles in responses to various stresses; however, their function is still not fully understood. Significant insight into their function can be obtained by analyzing their promoters. In the present study, the 5' upstream promoters (1000 bp) of 43 Asian rice (Oryza sativa var. Japonica) GLP genes were retrieved from the Plant Ensemble, based on the Rice Annotation Project database (RAP-DB). Phylogenetic analysis via MEGA6 showed a narrow genetic background (0.2%) with a Tajima neutrality value (π) of 0.69. Overall, 4234 transcription factor (TF) binding sites (TFBSs) were found on chromosomes 1, 2, 3, 4, 5, 8, 9, 11 and 12 via “MatInspector” from 90 different TF families using a total of 444. Common TFs and DiAlign analyses showed that Arabidopsis homeobox protein (AHBP), MYB-like proteins (MYBL) and vertebrate TATA-box-binding protein (VTBP) were the most abundant, common and evolutionarily conserved elements in the upstream region from 0 to -800. Finding their mutual interaction via Farmworker analysis uncovered three new cis-regulatory modules (VTBP_VTBP, MYBS_MYBS, and AHBP_VTBP), which appear to be decisive for OsGLPs regulation. In silico functional analysis via ModelInspector revealed 77 cis-regulatory modules, each comprised of two elements, among which DOFF_OPAQ_03 and GTBX_MYCL_01 were the most frequent and mostly found on chromosome 8 and 12, indicating that the combinatorial interaction of these elements has a fundamental role in various biological processes. The study revealed the importance of these elements in regulating the expression of OsGLPs that will help in predicting the role of these genes in various stresses and can have application in biotechnology. DOI: 10.2298/ABS151116076I Key words: TFBS; in silico; rice; germin-like proteins (GLPs); promoter Received: November 16, 2015; Revised: January 12, 2016; Accepted: January 19, 2016; Published online: September 20, 2016 How to cite this article: Ilyas M, Naqvi SMS, Mahmood T. In silico analysis of transcription factor binding sites in promoters of germin-like protein genes in rice. Arch Biol Sci. 2016;68(4):863-76.